Antimicrobial Activity of Leaf Extracts of Achyranthes aspera Linn. - SARAVANAN, P.; RAMASAMY, V.; SHIVAKUMAR, T. (Asian Journal of Chemistry, 2010)
Solvent leaf extracts of Achyranthes aspera Linn. was tested for its antibacterial and antifungal activities against the organisms, E. coli, Enterobacter sp. P. aeruginosa, P. vulgaris, S. aureus, Klebsiella sp. Salmonella sp. Shigella sp. Trichophyton mentagrophytes, T. rubrum, T. tonsurans, Aspergillus sp. E. floccosum. C. neoformans and Candida albicans. In the present study, maximum inhibitory activity was observed in diethyl ether extract against all the bacterial and fungal species.